Main Evil Figures In The Sequels To The Disney Classics - Monleón, Vicente (situArte, 2023)
Visual culture, specifically animated cinema, through this resource a set of concrete values is transmitted to the consumer society. In this plane, the American company Disney stands out. This study follows a mixed methodology to analyze the aesthetic and ethical characteristics that theproducer disseminates through the creation of its perverse figures and that help to understand the concept of “evil” presented by Disney. For this, the selected sample is a set of 19 feature films that are labeled as sequels to classic films. The findings manifest a continuation in the Manichaeism offered by Disney in its antagonistic, yet stereotyped figures. However, an explanation of their humanization is beginning to be noticed.